Initiation to research in Brazil: p olicies for educating young researchers - Lucídio Bianchetti; Adriano de Oliveira; Evellyn Ledur da Silva; Luiza Turnes (Universidade Federal de Santa Maria, 2012)
Scientific Initiation (SI) is a process which, through universities, challenges young people and provides them a set of attitudes and knowledge that is indispensable to their initiation to research, and the production and socializing of knowledge. Situated in the context of our broader research, this text is based on bibliographic research. It critically analyzes the importance of SI to qualify the approximation between basic education and undergraduate and graduate studies, given that the range of options of this mode of education has significantly expanded in recent years. Entrance into SI contributes in particular to theoretical grounding and to developing a familiarity with research methodology, complementing the academic training of young students with a process in which knowledge, in addition to being constructed in relation to teaching-research, comes to be re-evaluated and recreated, challenging young people to become researchers. Finally, we detect an increasingly evident instrumentalization of this locus of education and research by CAPES and CNPq, to improve evaluation indicators for undergraduate courses.